Indicators of the cytokine system in practically healthy women of different ages and interrelation with the emotional state - N. S. Chepurnova; O. N. Birko; S. V. Knysh; A. V. Rudneva; V. V. Zharskaya; A. E. Peskova; R. B. Mamedov (Медицинская иммунология)
Numerous studies show the role of the cytokine network in the pathogenesis of anxiety and depression. However, at present, studies of the correlation between the levels of pro-inflammatory and antiinflammatory cytokines and the level of emotional stress are rather few. The aim of the study was to analyze the serum levels of pro-inflammatory and anti-inflammatory cytokines and the emotional state in apparently healthy women depending on age. Serum levels were tested IL-1β, IL-6, IL-17, IFNγ, IL-10 and IL-4 in 100 apparently healthy women, who were divided into 3 groups depending on age (WHO): 18-44 (young age) 30 people, 45-59 (middle age) 40 people, 60-74 (old age) 30 people (sandwich variant of enzyme-linked immunosorbent assay, pg/mL). To assess the emotional component of health, all the subjects passed the questionnaire SF-36 “Assessment of the quality of life”. Statistical processing of the obtained data was carried out using the analytical software IBM SPSS Statistics, 22.0. In practically healthy women, an increase in the values of IL-1β and IL-6 was found in the elderly group (p < 0.05), while no differences were found between the groups of young and middle age. The level of IFNγ in all age groups of women did not differ significantly. At the same time, in the elderly group, the levels of IFNγ in 40% ranged from 1.04 to 8.76 pg/mL, and in 60% of women – from 24.85 to 28.5 pg/mL. IL-17 was also high (p < 0.05-0.01) in the group of women aged 60-74. In the anti-inflammatory link, the opposite picture was observed, for example, in young and middle-aged women, the levels of IL-10 and IL-4 were higher than in the elderly group. Thus, the analysis made it possible to state that the parameters of the cytokine profile and emotional state in women are associated with age.